Teachers’ representations of the ‘typical’ parent - Symeou, Loizos; Stylianou, Elena (International Journal about Parents in Education, 2023)
In this paper we present the findings of a study that investigates Greek-Cypriot teachers’ visual representations of parents typically encountered in the course of teachers’ daily professional practice. The study aims to identify which parents typically communicate with the school, to explore teachers-parents relationship as well as the ways in which parents’ representations relate to the various demographic sub-groups of families encountered in Greek-Cypriot schools. After we briefly describe the social and educational context in which the study was implemented, we present the methodology that we followed, and discuss how drawings by 72 Greek-Cypriot preand in-service teachers of different school levels and of different teaching experiences represent the ‘typical’ parent. This methodological approach was used to gather visual data, alternatively to traditional interviews or observations. We then describe how the drawings and their accompanied text were analysed. The analysis of the data indicates that teachers typically encounter mothers rather than fathers; parents of the local ethnic-cultural dominant group (Greek-Cypriots), and rarely parents from other ethnic-cultural groups; middle class parents rather than working class parents; and higher educated rather than lower educated parents. The analysis of the data also points out that teachers are highly concerned with parents’ image of them. We conclude by discussing how teachers’ images seem to reflect the broader local parent and family profile and how these data could potentially enhance understanding of school-family relationships, thus allowing for suggestions about the ways in which teachers could be supported for collaborating with all families of the children they teach.